Pruning ornamental trees - Autrey, Russell; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2000)
This program let us see how to safely use and maintain pruning tools as we demonstrate pruning on a variety of landscape trees. learn about thinning, shaping, shearing, heading back, undercuts, 3-point cuts and the proper angle of attachent for tree limbs. Learn the artistic and technical aspects of pruning ornamental trees
Title from title screen
Executive director, Joe Clokey
Narrated by Jora Clokey
DVD format
Keywords: Pruning; Ornamental trees